Targeted Therapy for Advanced Solid Tumors on the Basis of Molecular Profiles: Results From MyPathway, an Open-Label, Phase IIa Multiple Basket Study - Hainsworth, John D; Meric-Bernstam, Funda; Swanton, Charles; Hurwitz, Herbert; Spigel, David R; Sweeney, Christopher; Burris, Howard; Bose, Ron; Yoo, Bongin; Stein, Alisha; Beattie, Mary; Kurzrock, Razelle (Journal of clinical oncology, 2018)
Purpose Detection of specific molecular alterations in tumors guides the selection of effective targeted treatment of patients with several types of cancer. These molecular alterations may occur in other tumor types for which the efficacy of targeted therapy remains unclear. The MyPathway study evaluates the efficacy and safety of selected targeted therapies in tumor types that harbor relevant genetic alterations but are outside of current labeling for these treatments. Methods MyPathway ( ClinicalTrials.gov identifier: NCT02091141) is a multicenter, nonrandomized, phase IIa multiple basket study. Patients with advanced refractory solid tumors harboring molecular alterations in human epidermal growth factor receptor-2, epidermal growth factor receptor, v-raf murine sarcoma viral oncogene homolog B1, or the Hedgehog pathway are treated with pertuzumab plus trastuzumab, erlotinib, vemurafenib, or vismodegib, respectively. The primary end point is investigator-assessed objective response rate within each tumor-pathway cohort. Results Between April 1, 2014 and November 1, 2016, 251 patients with 35 different tumor types received study treatment. The efficacy population contains 230 treated patients who were evaluated for response or discontinued treatment before evaluation. Fifty-two patients (23%) with 14 different tumor types had objective responses (complete, n = 4; partial, n = 48). Tumor-pathway cohorts with notable objective response rates included human epidermal growth factor receptor-2-amplified/overexpressing colorectal (38% [14 of 37]; 95% CI, 23% to 55%) and v-raf murine sarcoma viral oncogene homolog B1 V600-mutated non-small-cell lung cancer (43% [six of 14]; 95% CI, 18% to 71%). Conclusion The four currently approved targeted therapy regimens in the MyPathway study produced meaningful responses when administered without chemotherapy in several refractory solid tumor types not currently labeled for these agents.